2022
DOI: 10.3390/microorganisms10061128
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiome Differences in Angus Steers with Differing Feed Efficiencies during the Feedlot-Finishing Phase

Abstract: The gastrointestinal microbiota of cattle is important for feedstuff degradation and feed efficiency determination. This study evaluated the fecal microbiome of Angus steers with distinct feed efficiencies during the feedlot-finishing phase. Angus steers (n = 65), fed a feedlot-finishing diet for 82 days, had growth performance metrics evaluated. Steers were ranked based upon residual feed intake (RFI), and the 5 lowest RFI (most efficient) and 5 highest RFI (least efficient) steers were selected for evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Since Paeniclostridium , Romboutsia , and Turicibacter belong to the Firmicutes phylum, a higher abundance of these genera in steers fed the late fattening TMR diet may contribute to the F/B ratio increase, which is positively correlated with the average daily gain [ 29 ]. This is supported by the association between Turicibacter and a high feed efficiency [ 11 , 37 ]. The increase in many minor bacterial species within Firmicutes may also contribute to the F/B ratio increase.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Since Paeniclostridium , Romboutsia , and Turicibacter belong to the Firmicutes phylum, a higher abundance of these genera in steers fed the late fattening TMR diet may contribute to the F/B ratio increase, which is positively correlated with the average daily gain [ 29 ]. This is supported by the association between Turicibacter and a high feed efficiency [ 11 , 37 ]. The increase in many minor bacterial species within Firmicutes may also contribute to the F/B ratio increase.…”
Section: Discussionmentioning
confidence: 96%
“…Alistipes is a core genus that is commonly found in the feces of cattle, but its function requires further investigation [ 7 , 16 , 36 ]. Previous studies showed that Turicibacter is more abundant in cattle with a high feed efficiency [ 11 , 37 ]. Since steers have a greater average daily gain compared to heifers, the abundance of Turicibacter is thought to be the greatest in Hanwoo steers fed a late fattening diet in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to findings for the rumen, there is a possible link between feed efficiency and the fecal microbiota in cattle. Some studies indicated that the fecal microbiota composition differed between high- and low-feed efficiency cattle [ 54 , 55 ]. Lourenco et al [ 54 ] compared fecal microbiota between efficient and inefficient Angus steers during the feedlot-finishing stage.…”
Section: Assessment Of Fecal Microbiotamentioning
confidence: 99%
“…Some studies indicated that the fecal microbiota composition differed between high- and low-feed efficiency cattle [ 54 , 55 ]. Lourenco et al [ 54 ] compared fecal microbiota between efficient and inefficient Angus steers during the feedlot-finishing stage. Their results showed that Ruminococcaceae and Clostridiaceae were decreased in inefficient Angus steers, whereas Peptostreptococcaceae and Turicibacteraceae were increased in efficient Angus steers during the feedlot-finishing stage ( Table 1 ).…”
Section: Assessment Of Fecal Microbiotamentioning
confidence: 99%